Exploring The Role of Grit and Self-Efficacy in Improving Teachers' Psychological Performance - Jamilah, Siti; Lailla, Nor; Nugroho, Wawan Sadtyo (Fakultas Ekonomi, Universitas Negeri Jakarta, Indonesia, 2025)
In the world of education, work engagement is one of the important factors that determine the quality of teacher performance in carrying out their professional duties. Teachers who have a high level of work engagement tend to be more dedicated, energetic, and fully involved in teaching activities. The purpose of this study was to determine the effect of: (1) Grit on Work Engagement; (2) Self Efficacy on Work Engagement; and (3) the effect of Grit on Self Efficacy. Research method This study used a non-experimental quantitative design with a survey approach. The population in the study were teachers at SMK Negeri 9 Tangerang. Samples were taken using the census method. Data collection used Google Forms. Data was analyzed using SmartPls. This method was chosen to test variables and is more flexible for limited sample sizes. The results of the study showed that grit had an effect on work engagement and self-efficacy. However, self-efficacy did not affect work engagement.